2021
DOI: 10.2147/bctt.s306971
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Annona muricata Fruit and Bee Venom Against MNU-Induced Breast Cancer in Pregnant Rats and its Complications on the Ovaries

Abstract: Aim: To evaluate the potential therapeutic role of Annona muricata (graviola) fruit and bee venom (BV) against N-methylnitrosourea (MNU)-induced breast cancer in pregnant female rats and complications in the ovaries. Methods: A total of 24 female rats were induced with a single dose of MNU (50 mg/kg body weight). After confirmation of positive tumor marker, female rats were placed with the males for mating. The pregnant rats were randomly divided into four groups (n=6): MNUinduced only (group 1), MNU-induced r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Inhibition of colorectal cancer metastases growth in the mice model under the influence of melittin was observed by Rocha et al [79]. Restoration of histological changes in ovarian and breast cancer rat models together with decreasing of serum MMP-1, reduction of NF-κB, and TNF was described by El-Beltagy et al [80].…”
Section: Apoptosismentioning
confidence: 90%
“…Inhibition of colorectal cancer metastases growth in the mice model under the influence of melittin was observed by Rocha et al [79]. Restoration of histological changes in ovarian and breast cancer rat models together with decreasing of serum MMP-1, reduction of NF-κB, and TNF was described by El-Beltagy et al [80].…”
Section: Apoptosismentioning
confidence: 90%
“…BV alone and in combination with other drugs or solutions had an anti-breast cancer impact (Khamis et al, 2018;Arani et al, 2019;El-Beltagy et al, 2021). In vitro, BV inhibited the growth of MCF7 and T47D cells, while blocking the cell cycle in the G2/M phase.…”
Section: Anti-breast Cancer Researchmentioning
confidence: 98%
“…Moreover, increasing evidence from animal studies indicates the safety of venom doses effective in in vitro studies [47]. Studies done mainly on mice and rats using both whole BV and MEL indicated inhibition of tumors and metastasis growth, suppression of tumor proliferation, inhibition of angiogenesis, reduction of tumor size, and induction of apoptosis [195][196][197][198][199][200]. To the best of our knowledge, currently, there have been no clinical trials on humans that could confirm the clinical effectiveness of bee venom and evaluate the safety of its administration concerning cancer treatment, although there have been several clinical trials either completed or recruiting for other disorders which are registered at https://clinicaltrials.gov/ (Accessed on 5 February 2024).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%